MEMAKNAI RITUAL TASAEB BANU DALAM PERSPEKIF LAUDATO SI DI DESA NOEPESU - Rachela Tefa, Maria; Asa Siri, Theodorus; Binsasi, Frederikus (Kanisius, 2024)
Culture is everything that individuals acquire from society, including beliefs, customs, artistic norms, eating habits, where the skills acquired are not from their own creativity but from the heritage of the pst obtainet through formal and informal education. Humans and culture are unity that will never be separated. Even though humans will die, their culture. However, in reality, many incidents that we find such as illegal logging wich has an impact on environmental damage. Therefore, though the Church love the environment where we liv, namely the Encyclical Laudato Si with the intention that we appreciate and preserve the environment as our place of residence, namely a place where our culture can grow and develop. Talking about culture means talking about the procedures and customs carried out by people, especially what we want to discuss here is the culture of the Timorese people related to environmental sustainability, namely the Tasaeb Banu ritual. This ritual is carried out with the aim that the people of Noepesu village appreciate nature more by not cutting down trees indiscriminately which can have a negative impact on the community itself. The purpose of writing this thesis is to find out the meaning of the Tasaeb Banu ritual as a ritual to maintain environmental sustainability as contained in the Laudato Si encyclical. The method usedin this study is a qualitative research method with a field study type. Based on the results to prohibit the people of Noepesu village from cutting down tres and damaging nature. Second, the Tasaeb Banu ritual is related to the Laudato Si encyclical on protecting and preverving the environment.